The Effect Of Ginger Drinking On Cardiovascular Endurance In FIKK UNM Futsal Club Players - Hasmyati; Nur Indah Atifa Anwar (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to determine the effect of ginger drink on cardiovascular endurance in futsal club players Faculty of Sports Sciences Makassar State University (FIK UNM). Cardiovascular endura nce is one of the important aspects that affect athlete performance, and ginger is known to have th e potential to increase body capacity through antioxidant and anti-inflammatory properties. The re search method used in this research is quasi-experiment with pre-test design and post-test Control Group Design. The sample consisted of 20 futsal players divided into two groups: control group (n =10) and treatment group given ginger drink (N =10). Cardiovascular endurance data were mea sured using standard methods before and after the intervention. The data analysis was done by ind ependent sample t-test to determine the significant differences between the two groups. The result s showed that the average cardiovascular endurance of the control group was 41,58 with a signific ance value of 0,038, while the average treatment group was 36,54 with a significance value of 0,0 41. The average difference in cardiovascular endurance between the two groups was 5,04, which s howed significant differences.